Welder Recruitment Decision Support System Using the SMARTER Method - Wahyuni Fithratul Zalmi; Bernad J. D. Sitompul; Sastra Wandi Nduru; Sedihati Kayan Lumbangaol (CV. Media Digital Publikasi Indonesia, 2023)
The high level of competition in the world of welding services business today makes the welding workshop entrepreneurs struggle hard to optimize the human resources as the welders own. The task is to recruit a skilled worker. This is due to the fact that the company is able to compete in the world of business services, the manufacturer of welding is very interested in the quality of the product so that the consumer is interested in improving the services offered by the business owner. In this study, to support the results of decision-making made in the recruitment process of welders, the SMARTER method is applied. On the final results of this study can be seen that the results of the application of the SMARTER method for comparison with 5 alternatives that are selected, that is, who obtained the first ranking is Joko with a value of 1.74. Then in the next ranking position is Tian (1.56) as the second ranking, Rian (1.06) third rank, Raden R (0.88) fourth ranking, and Budi Ramadhan (0.36) in the last ranking position